Establishment of a multicomponent quality control method and the transfer characteristics of five markers from Qidongning Formula to rat tissues by HPLC-QQQ-MS/MS - Zhou, Di; Chen, Jian-Ru; Yang, Zi-Qi; Xu, Ling; Huang, Yu-Feng (Frontiers in Pharmacology, 2023)
Traditional Chinese medicine compound preparations have become an increasingly utilized strategy for tumour treatment. Qidongning Formula (QDN) is a kind of antitumour compound preparation used in hospitals, and it can inhibit the growth of lung cancer cells. However, due to the complexity of botanical drugs, the quality evaluation of QDN is inconsistent, affecting clinical efficacy and posing potential safety risks for clinical application. Additionally, tissue distribution is an integral part of the drug development process. Hence, to study the distribution characteristics of markers in compound preparations and rat tissues, a novel HPLC-QQQ-MS/MS quantitative analytical method was established to determine five markers in QDN simultaneously, and the method was verified. The analytical results showed that the contents of salidroside (51.6±5.75 μg/g), calycosin-7-O-β-D-glucoside (94.2±15.4 μg/g), specnuezhenide (371±72.5 μg/g), formononetin (23.8±5.39 μg/g), and polyphyllin I (87.7±10.6 μg/g) were stable in different batches of QDN. After intragastric administration (13.5 g/kg) in rats for 1 h, four markers in the QDN, except polyphyllin I, were distributed in most tissues. QDN was distributed chiefly in the stomach and small intestine, followed by the liver or kidney. The study also found that specnuezhenide had the highest concentration in both QDN and rat tissues (102±22.1 μg/g in the stomach), while formononetin had the highest transfer rate (0.351%) from QDN to rat intestines. The above research lays a quality research foundation for the antitumour application of QDN and provides a scientific reference for the quality control of Chinese medicine compound preparations.